ED to EPI: protocol for a pragmatic randomised controlled trial of an SMS (text) messaging intervention to improve the transition from the emergency department to early psychosis intervention for young people with psychosis. Issue 12 (17th December 2020) - Polillo, Alexia; Foussias, George; Wong, Albert H C; Ampofo, Augustina; Stergiopoulos, Vicky; Anderson, Kelly K; Bromley, Sarah; D'Arcey, Jessica; de Oliveira, Claire; Duda, Lillian; Henderson, Joanna; Kidd, Sean; et al.
Abstract : Introduction: While nearly half of all new psychotic disorders are diagnosed in the emergency department (ED), most young people who present to the ED with psychosis do not receive timely follow-up with a psychiatrist, and even fewer with evidence-based early psychosis intervention (EPI) services. We aim to test an intervention delivered using short message service (SMS), a low-cost, low-complexity, youth-friendly approach, to improve transitions from the ED to EPI services. Methods and analysis: This is a protocol for a pragmatic randomised, single blind, controlled trial with accompanying economic and qualitative evaluations conducted at the Centre for Addiction and Mental Health (CAMH) in Toronto, Canada. A consecutive series of 186 participants aged 16–29 referred by the ED to CAMH's EPI programme will be recruited for a trial of a two-way intervention involving reminders, psychoeducation and check-ins delivered via SMS. The primary outcome will be attendance at the first consultation appointment within 30 days of study enrolment assessed through chart reviews in the electronic health record. We will also extract routine clinical measures, including the Brief Psychiatric Rating Scale, Clinical Global Impression and Service Engagement Scale, and link with provincial health administrative data to examine system-level outcomes, including ED visits and psychiatric hospitalisations, 6 months and up to 2 years after baseline. We will perform a cost-effectiveness analysis of the primary study outcome and costs incurred, calculating an incremental cost effectiveness ratio. Web-based surveys and qualitative interviews will explore intervention user experience. Patients and families with lived experience will be engaged in all aspects of the project. Ethics and dissemination: Research Ethics Board approval has been obtained. Findings will be reported in scientific journal articles and shared with key stakeholders including youth, family members, knowledge users and decision makers. Trial registration number: NCT04298450 .